CARBON CAPTURE AND UTILIZATION: DEVELOPING TECHNOLOGIES TO CAPTURE AND UTILIZE CO₂, SUCH AS CARBON CAPTURE AND STORAGE (CCS) OR CARBON UTILIZATION: CASE STUDY OFNORWAY, CANADA AND USA - Muhammad Muzamil Khan,; Muhammad Yasir,; Dr. Imran Khan Swati,; Mushtaq Ahmad,; Isra Waseem,; Basit Ali, (Spectrum of Engineering Sciences, 2025)
Increasing levels of carbon dioxide (CO₂) in our atmosphere from what people do is the main factor leading to climate change. For this reason, greater consideration is being given to CCU technologies in the ongoing aim to cut global greenhouse gas emissions and move to a reliable low-carbon economy. CO₂ is first taken out of industrial and energy-related processes and is then converted into valuable goods or kept for a long time. Such strategies cover methods called CCS and several ways to use carbon which can each help lessen climate change and help industries become more sustainable. Many people separate carbon capture into pre-combustion, post-combustion and oxy-fuel combustion types. The main reason post-combustion capture is widely used in industries and power plants is that it fits well with current equipment. CO₂ that is captured can either be locked up in underground places such as depleted oil and gas wells and deep salty underground water (CCS) or be used to support oil and gas production (EOR) as well as the making of synthetic fuels, polymers, concrete and various other chemicals. Using carbon to produce chemicals and fuels has gained interest because it helps limit greenhouse gases and creates products that can be sold. The recent progress in chemical engineering, materials science and catalysis has helped make the capture and conversion of carbon dioxide both faster and more cost-efficient. Using advanced sorbents, membranes and solvents has led to better collection of CO₂ and promising new electrochemical and photochemical routes are coming up for converting it. Even so, the use of CCU is not without problems, since it requires a lot of money, energy, new infrastructure and the outcome of CO₂-derived products is not clear. Life cycle assessments (LCAs) are important so that businesses can confirm that using carbon is beneficial to the environment and does not cause environmental damage in other parts of the supply chain. For these barriers to be overcome, it is necessary to have policy help, team up with private companies and invest in specific research projects. Governments and such organizations are paying more attention to CCU as a way to achieve zero net emissions, as demonstrated by the U.S. Department of Energy’s Carbon Negative Shot and the Green Deal launched by the European Union. Additionally, uniting CCU technology with energy sources like solar and wind is likely to help industrial processes produce less carbon and contribute to a renewed carbon economy. All in all, using carbon capture and utilization technologies could solve climate change while ensuring industry is sustainable. More innovation, suitable policies and teamwork on a global scale help make CCU play its intended role in addressing climate change. Carbon capture and utilization (CCU) involves turning CO₂ into goods, resources or energy and is known as CCU.